The Role of Good Governance’s Legal and Institutional Frameworks in Protecting Human Rights: From Theory to International Practice - Hadjab, Abdelghani; Belouadah, Tayeb (Journal of Legal Studies and Researches, 2026)
This paper aims to synthesize these diverse threads of scholarship, providing a comprehensive analysis of how good governance, through its robust legal and institutional frameworks, specifically acts as a catalyst for enhancing and protecting human rights. The study will address both the theoretical underpinnings that connect these two vital concepts and the practical mechanisms through which their synergy can be maximized. This academic article employs a qualitative, analytical, and descriptive research methodology. The primary approach involves a comprehensive review and synthesis of existing scholarly literature and international documents pertaining to good governance and human rights. The research process includes a thematic analysis of the provided research material, systematically identifying key concepts, definitions, principles, historical developments, interrelationships, and impacts relevant to both good governance and human rights. This method allows for the extraction and interpretation of complex connections, including underlying trends and broader implications, to provide a deeper understanding of the subject matter.